Improving vocational students’ learning outcomes through an innovative instructional model: A quasi-experimental study - Saifuddin Karim; Muhammad Indra (Jurnal Pendidikan Vokasi, 2025)
Vocational learning requires instructional strategies that actively engage students in authentic problem-solving and skill development. However, many classroom practices still rely on conventional approaches that provide limited opportunities for exploration and collaboration. This study investigates the effect of the implemented learning model on students’ learning outcomes and skill performance in a vocational education setting. A quasi-experimental design with pretest–posttest control groups was employed. Participants consisted of students enrolled in the targeted subject, divided into experimental and control classes. Data on cognitive learning outcomes and performance skills were collected using validated tests and observation sheets. The data were analyzed using descriptive statistics and inferential tests to examine differences between groups and effect sizes. The findings show that students in the experimental class achieved significantly higher posttest scores than those in the control class. In addition, their skill performance increased from the “moderate” to “high” category, while the control group improved only slightly. These results indicate that the learning model provides structured guidance, promotes active participation, and encourages reflection, thereby supporting stronger conceptual understanding and more consistent practice performance. The study highlights the importance of integrating student-centered strategies in vocational classrooms to bridge the gap between theory and practice. Practical implications include the need for teacher training, structured lesson design, and supportive assessment systems to sustain the effectiveness of the model.